Achievements and Barriers in Evaluating Stunting Prevention Programs in Keboguyang Village, Indonesia - Santoso, Suwandi Iwan; Rodiyah, Isnaini (Indonesian Journal of Cultural and Community Development, 2024)
Background: Stunting is a significant global health issue, with Indonesia's prevalence reaching 21.6% in 2022, particularly alarming in Keboguyang Village, Jabon District, where the stunting rate stands at 10%. Specific Background: Despite allocating 10% of village funds for stunting prevention, the persistence of high rates necessitates a critical evaluation of current interventions. Knowledge Gap: Limited research exists on the implementation effectiveness of stunting prevention programs at the village level in Indonesia, particularly regarding communication, resource allocation, and bureaucratic structure. Aims: This study aims to evaluate the implementation of stunting prevention programs in Keboguyang Village using Edward III's (1980) theory of policy implementation, focusing on the factors influencing success or failure. Results: Utilizing qualitative descriptive methods, data were collected through field observations, interviews with key informants—including the village head, midwife, health cadres, and mothers—and documentation analysis. The findings reveal effective communication strategies through door-to-door outreach and child data collection, alongside strong commitment from local leadership. However, challenges arise from insufficient incentive regulations, limited human resources, and infrastructural deficiencies. Novelty: This research contributes new insights into the multifaceted nature of stunting prevention efforts at the community level, highlighting specific barriers that need addressing. Implications: The study underscores the need for enhanced human resources and infrastructural support to bolster the effectiveness of stunting prevention initiatives, providing valuable recommendations for policymakers and community health programs aimed at reducing stunting rates in Indonesia. Highlights: High Stunting Rates: Keboguyang Village has a 10% stunting prevalence. Evaluation Framework: Edward III's theory evaluates program implementation effectiveness. Resource Challenges: Limited human resources hinder stunting prevention efforts. Keywords: Stunting, Indonesia, Health Policy, Community Development, Implementation